Periplasmic production of the recombinant ‎eugenol synthase from Ocimum basilicum - Neda Mazarei; Anahita Moradi; Seyyed Soheil Rahmatabadi; Shiva Hemmati (Shiraz University of Medical Sciences, 2019)
Eugenol, the main bioactive compound of clove oil, is a simple molecule with considerable pharmacological properties, including analgesic, antimicrobial, and anti-inflammatory effects. Eugenol is synthesized in several plant species such as Ocimum basilicum (basil) through the activity of eugenol synthase enzyme. Regarding the valuable applications of eugenol as well as notable advantages of the secretory production of recombinant proteins, the excretory production of eugenol synthase has been targeted in this study. Eugenol synthase coding sequence was inserted after pelB peptide in the pET22b vector and expressed in E. coli to investigate if the secretory production of the recombinant protein is possible. Additionally, enzyme purification by Ni-NTA affinity chromatography, extraction of the enzyme from periplasmic fraction, and salting out of the enzyme secreted into the medium by ammonium sulfate precipitation were carried out. Our results showed the presence of eugenol synthase in the cytosol, periplasm, and culture medium with concentrations of about 208.8 µgml-1, 212.5 µgml-1, and 332.0 µgml-1, respectively. The results of this study are useful for further studies to produce large-scale eugenol synthase as an unlimited source of the eugenol compound.